OPTIMIZATION OF MALUKU'S DIRECTORATE GENERAL OF CUSTOMS AND EXCISE SUPERVISION FUNCTION IN THE ARCHIPELAGIC REGIONS FOR EXCITED GOODS CIRCULATION - Ahmad Mufti; Muhaimin Limatahu (Cepalo, 2022)
The Directorate General of Customs and Excise is engaged in customs and excise. Meanwhile, as the technical implementer at the district/city level, the Customs Supervision and Service Office has the task of carrying out the formulation and implementation of policies in the field of supervision, law enforcement, service, and optimization of state revenues in the customs and excise sector following the provisions of laws and regulations. The general goal of this research is to determine the extent to which the Ternate Office of the Directorate General of Customs and Excise implements the supervisory function in supervising the circulation of excisable goods and other contraband goods in the North Maluku community, while the specific goal of the study is to determine the efforts optimization carried out by the Ternate Office of the Directorate General of Customs and Excise. Furthermore, studies revealed that the Ternate Office of the Directorate General of Customs and Excise continues to improve its performance to optimize the internal control function of excisable goods as measured by Key Performance Indicators and collaboration between institutions such as the Operational Facility Base, the Indonesian Navy, the Indonesian Amy, the Indonesian Air, and Water Police, the National Narcotics Agency or Badan Narkotika Nasional (BNN), the Ministry of Tr, and the Ministry of Tr. The most noticeable obstacle is the number of personnel and facilities spreading across the vast area being monitored, the strategic area of the North Maluku waters, community and cultural factors.